Pengaruh Model Learning Cycle 7E terhadap Keterampilan Menulis Teks Biografi Siswa Kelas X SMA Negeri 2 Medan - Sianturi, Hanna Allora (YASIN, 2025)
This study was motivated by the low biographical text writing skills among Grade X students at SMA Negeri 2 Medan, which is partly attributed to the lack of variety in instructional models. The purpose of this research is to examine the effect of the Learning Cycle 7E model on students’ biographical writing skills. A quantitative method was used with a quasi-experimental design. The research sample consisted of 35 students selected through classify random sampling. Data were collected through observation, interviews, documentation, and writing tests. The results showed that the average student writing score increased from 71 before the treatment to 82 after the implementation of the Learning Cycle 7E model. The t-test revealed a result of tcount = 5.275 > ttable = 2.04, with a significance value of 0.000 < 0.05, indicating a significant effect of the Learning Cycle 7E model on students’ ability to write biographical texts. These findings suggest that the application of a learning model focused on exploration and reflection stages, such as Learning Cycle 7E, can serve as an innovative instructional strategy to effectively enhance students’ writing skills.